A Case Study on the Efficacy of Navaprasrutik Basti in the Management of Janu Sandhigata Vata (Knee Osteoarthritis) - Yadav, Garima; Singh, Gyanendra; Gaurav, Shubham; Yadav, Deepak (International Research Journal of Ayurveda & Yoga, 2025)
The elderly is prone to the condition known as Sandhigata Vata (osteo arthritis). Some of the risk/cause factors include lifestyle choices, excessive weight, trauma, and a diet lacking in calcium. Vata is vitiated by Rooksha Aahar (dry diet) and Ativyaam (excessive exercise). It mostly affects the body’s weight-bearing joints, particularly the knee, hip, and lumbar spine. The most prevalent type of articular problems, Sandhigata Vata (osteo arthritis), severely restricts a sufferer’s ability to walk, dress, bathe, and do other daily tasks. The condition frequently manifests as Shula (pain), Shotha (swelling), Vata Poornadriti Sparsha (crackling sound), and trouble flexing and extending the Sandhi (joints). Calcium supplements, and ultimately joint replacement, are all alternatives for therapy. Here in this case study, a 41-year-old patient with Janu Sandhigata Vata (osteo arthritis) came with complaints of Right Knee joint pain, crackling sound in joints for 1.5 months. Due to long standing and straining, the patient had these symptoms. This indoor patient received 10 days of Anuvasana with Murchhita Tila Taila (medicated oil) and Navaprasrutik Basti (enema) and 10 days of Abhyanga (massage) at Nabhi (umbilicus), Parshva (flanks), Prushtha (back), and Ubhayapada Pradesh. The patient reacted favorably to these Ayurvedic therapies and had significant symptoms of alleviation.